The uses of photography in Ireland 1839-1900 - Slattery, Peadar (Trinity College (Dublin, Ireland). Department of History, 1992)
Professional photography was introduced to Ireland in 1841 and accepted change contemporaneously with London trends. It expanded in the cities and towns with Belfast and Dublin becoming major centres. By 1881 most counties in Ireland had at least one photographer. Photography provided employment; there were 677 persons in photography in 1901, one third of whom were female.
Access restricted on volume 3 due to image copyright concerns. Please consult print copy in the Library.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin